Tension-controlled suburethral synthetic sling versus standard sling in the treatment of female stress urinary incontinence: preliminary short-term results - G. R. Kasyan; O. R. Aliev; D. Yu. Pushkar (Вестник урологии, 2025)
Introduction. Suburethral sling surgery has been successfully used for the treatment of female urinary incontinence (UI) for several decades. In addition to high efficacy, there are unresolved problems associated with the high recurrence rate of UI and re-emerging lower urinary tract symptoms associated with iatrogenic infravesical obstruction. Tension standardisation may be the key to further improving the outcomes of UI-patients.Objective. To compare the results of surgical treatment of stress urinary incontinence (SUI) using a tension-controlled synthetic sling with standard suburethral sling surgery. Materials & methods. We conducted a randomised trial to evaluate the efficacy of surgery with tension-controlled synthetic loops (ClinicalTrials.gov no. NCT04101279). The middle portion of the loop has an absorbable damping layer that contacts the urethral mid-third, thereby providing standardised loop tension. Through block randomisation, patients were included in the study group and underwent surgery using a suburethral loop with a tension control device. The control group underwent surgery using a synthetic Urosling loop (Lintex®). All patients underwent standard examination before hospitalisation and after surgical treatment, including chairside examination. The stages of functional assessment of the patients' condition included assessment by the UDI-6 and IIQ-7 questionnaires, preoperatively and postoperatively at 1 and 3 months, as well as urodynamic examination before and after surgery.Results. Overall, 280 patients were screened and signed informed consent to participate in the study. We enrolled 253 patients randomised into two groups: group 1 (study group) included 123 patients and group 2 (control group) included 130 patients. The mean age of the study participants in the study group was 55.2 ± 10.9 years, the mean BMI was 25.60 ± 2.55, and the mean length of urinary incontinence was 4.47 ± 3.79 years. According to the questionnaires (UDI-6, IIQ-7) after one month, the improvement of indicators was significant improvement in symptoms in both groups, while group to group comparison showed no difference. Based on urodynamic study three months after treatment, recurrence of SUI was noted in 6.6% of patients in the study group, while in the control group in 8.0%. Urge UI occurred de novo was noted in 4.9% of patients in the main group vs in 10.0% in the control group.Conclusion. The tension-controlled synthetic suburethral loop has advantages over the traditional standard loop in the treatment of female SUI regarding the reduction of the incidence of infravesical obstruction, prosthesis protrusion, and the incidence of recurrent lower urinary tract symptoms. This is achieved by standardising the sling implantation step and preventing excessive or insufficient loop tensioning. This technique can be used in day-to-day urological practice.